2018
DOI: 10.3390/nu10121980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wheat Bran on Fecal Butyrate-Producing Bacteria and Wheat Bran Combined with Barley on Bacteroides Abundance in Japanese Healthy Adults

Abstract: Wheat bran (WB) is rich in insoluble arabinoxylan, while BARLEYmax (BM) is a barley line that is rich in fructan, resistant starch, and β-glucan. In the present study, we investigated which of these two fiber sources would produce more favorable changes in the fecal variables of healthy subjects. Sixty healthy subjects were randomly divided into four groups (n = 15 per group) and fed twice daily for 4 weeks with baked cereal bars containing neither WB nor BM (WB−BM−), WB without BM (WB+BM−), BM without WB (WB−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Similar to Anaerotruncus, Anaerostipes is a butyrate-producing genus that is associated with the gut microbiota of healthy individuals (58,59). Anaerostipes has been reported to decrease in abundance in HFD-induced metabolic syndrome (60), and to increase after low-fat vegetarian diets (61) and fiber-rich diets (62) and also when the BMI decreases (63), in agreement with the data obtained in the present study. Ruminococcaceae have been shown to negatively correlate with metabolic disease in humans (64), and we observed that the genus Ruminococcaceae (UCG-014) negatively correlated with SFAs consumption.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to Anaerotruncus, Anaerostipes is a butyrate-producing genus that is associated with the gut microbiota of healthy individuals (58,59). Anaerostipes has been reported to decrease in abundance in HFD-induced metabolic syndrome (60), and to increase after low-fat vegetarian diets (61) and fiber-rich diets (62) and also when the BMI decreases (63), in agreement with the data obtained in the present study. Ruminococcaceae have been shown to negatively correlate with metabolic disease in humans (64), and we observed that the genus Ruminococcaceae (UCG-014) negatively correlated with SFAs consumption.…”
Section: Discussionsupporting
confidence: 90%
“…Measurement of short-chain fatty acids—acetic acid, propionic acid, butyric acid, lactic acid, and succinic acid—in fecal samples was performed at the TechnoSuruga Laboratory, Co., Ltd. (Shizuoka, Japan). For the determination of these short-chain fatty acids, feces were suspended in distilled water, heated at 85 °C for 15 min to inactivate viruses, and then centrifuged according to previously reported methods 40,41 . The concentrations of these short-chain fatty acids in feces were measured using a high-performance liquid chromatography organic acid analysis system with a Prominence CDD-10A conductivity detector (Shimadzu, Kyoto, Japan), two tandemly arranged Shim-pack SCR-102(H) columns [300 mm × 8 mm inner diameter (ID)], and a Shim-pack SCR-102(H) guard column (50 mm × 6 mm ID) 40,41 .…”
Section: Methodsmentioning
confidence: 99%
“…Cecal contents were collected at the sacrifice and immediately frozen. SCFAs concentrations were quantified by HPLC using a post column reaction with a Prominence CDD-10Avp conductivity detector (Shimadzu, Kyoto, Japan), tandemly arranged two columns (Shim-pack SCR-102(H); 300 mm × 8.0 mm ID), and a guard column a Shim-pack SCR-102(H) guard column (50 mm × 6.0 mm ID) as mentioned previously [28].…”
Section: Analysis Of Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%